The Evolving Indo-Pacific Region: An Introduction to External Perspectives on Africa’s Role and Position (The Strategic Review for Southern Africa, 2022)
This article explores the evolution of the ‘Indo-Pacific’ as a concept and geopolitical social construct. Since 2007, the concept has been framed predominatly to fit the geostrategic concerns of global North powers, however, contrary to this slant taken by an array of recent Indo-Pacific strategies, the concept itself is historically rooted in ideas of anti-colonial politics, social justice, developmentalism and cooperation. Regional Security Complex (RSC) theory is applied as a useful conceptual framework and demonstrates how security problems and concerns are intimately tied to others and is thereby relational. Indeed such a theory will need to increasingly account for ocean regions, away from a terra-centric focus. Finally the article explores the role of political geography. While the security complex in this mega-region is defined by particular states, the physical boundaries remain open to interpretation, based on a state’s view of itself and its geography, as well as how it makes sense and projects its changing interests. It is for these menrtioned reasons that the western Indo-Pacific and African littoral states remain unevenly accounted for.